(3QSGdI aj Yde GdehSjbis
(3ChdgG (B:s
(3HYO GdHSedI(B: (3Je fYeJc YdjfG GdehSjbi Yde jHMK ajg Yf CMhGd GdfZe ef MjK jJCda hjJfGaQ s
(3BNQgG (B:s
(3hPdc EPG GfbSe GdPiHGdCQHY HQHY efg , hQHY eOg heOJi hGddg CYde hgh CMce hGdMeO ddg , QH GdYGdejf hUdhGJg Ydi CfHjGFg CLeYjf s
(3jdjgG HYV UaMGJ ai GdEjbGYGJ GdehSjbjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeO GdKGdK HGSJGfHhd (B(3449) s
Keywords: (3GdehSjbi hGdZfGAs